Speed controller of servo motor for industrial purpose - Wan Mohd Norhasmi Wan Hashim (School of Electrical System Engineering, University Malaysia Perlis, 2011)
This project is mainly about constructing a DC motor speed controller using microcontroller PIC 16F877A. It is an open loop control system where the output motor speed signal is feedback to the controller by using an encoder sensor. The PIC 16F877A is programmed by using MPLAB software via C language. The program consists of the PWM signal, rotary encoder speed readings, and the LCD display.Pulse Width Modulation (PWM) technique is used where its signal is generated within the microcontroller. The microcontroller then acts as the controller in this project. The generated PWM signal was sent to motor driver to generate new input voltage for the DC motor. Then, the new desired speed is achieved. With the project data and observation, it can be conclude that the speed control project objective was achieved where, the DC motor speed can be control by using the PWM duty cycle control method.